Biobetter Versions of Recombinant Human IFN-α2b for the Treatment of Viral Infections - Mufarrege, Eduardo Federico (2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the infectious agent causing COVID-19 disease, whose pandemic has had far-reaching consequences on the global population. Since the detection of the first cases in late 2019, much has been learned about the mechanism of action of SARS-CoV-2 and the associated immune response to eradicate the infection. Recently, a clear correlation between disease severity and abnormal type I IFN response in patients has been established. Individuals with immune responses characterized by high concentrations of IFN-a2b and low blood levels of IL-6, TNF-alpha, and IL-1Ra were much less affected than those patients who exhibited an opposite scenario. Interestingly, recombinant human IFN-a2b (rhIFN-a2b) could mitigate the severity of symptoms, if given in the early stages of the disease, before reaching the inflammatory shock (cytokine storm) that characterizes the most severe cases. However, there are adverse effects associated with rhIFN-a2b-based therapy. Among them, the emergence of unwanted immune responses against the biologic can, in some cases, compromise the treatment’s safety and efficacy. In addition, rhIFN-a2b is a small cytokine, which results in rapid clearance from the bloodstream. This quick plasma clearance poses the need for frequent high doses to achieve the desired effect, which may, in turn, exacerbate unwanted effects associated with therapy.In this article we will address the most relevant strategies for the development of biobetters versions of rhIFN-a2b, as promising candidates for the treatment of COVID-19 and other human viral diseases.